Pengaruh Pendidikan Disiplin Rohani dalam Keluarga Berdasarkan Ulangan 6:6-9 Terhadap Kecerdasan Emosional dan Improvisasi Sosial Siswa-Siswi Kelas IX SMP Unggul Sakti di Kota Jambi - Yohan Liem (ILLUMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2021)
Measurable, systematic, and directed teaching in terms of spiritual discipline of children is found in the Bible, namely in the Book of Deuteronomy 6:6-9. The aims of this study were to: 1) describe the role of spiritual discipline education in the family based on Deuteronomy 6: 6-9, emotional intelligence and social improvisation skills of Class IX Unggul Sakti Junior High School students, 2) Test how far the spiritual discipline education in the family is based on Deuteronomy 6: 6-9 plays a significant role and affects the emotional intelligence and social improvisation abilities of Class IX Unggul Sakti Junior High School students, 3) Analyzing how the influence of spiritual discipline education in the family based on Deuteronomy 6: 6-9, on the emotional intelligence and social improvisation abilities of Class IX Unggul Junior High School students Magic. The sampling technique is purposive sampling. Based on the results of the study, it can be concluded that spiritual discipline has a positive and significant effect on students' emotional intelligence and social improvisation as indicated by the probability value <0.05) (0.000<0.05). Adjusted R Square value is 0.204. This shows that 20.4% of students' emotional intelligence and social improvisation are influenced by spiritual discipline, while the remaining 79.6% is influenced by other factors not explained in this study.